COMPARISON OF K-NEAREST NEIGHBOR, MULTIPLE LINEAR REGRESSION, AND RANDOM FOREST CLASSIFIERS FOR DEPTH EXTRACTION IN THE SHALLOW WATER OF KEPULAUAN SERIBU, INDONESIA - Rifqi Muhammad Harrys, Ratna Sari Dewi; Teguh Sulistian; Dimas Hanityawan Suryopuspito; Fajar Triady Mugiarto (Badan Informasi Geospasial, 2023)
Satellite-derived bathymetry is a method used to overcome the limitation of survey vessels when acquiring depth data in shallow waters of less than 2 m, especially depths of 0-2 m. Currently, the SDB method has been widely used to provide shallow water bathymetric data. Besides this method can provide wide coverage of depth data, the availability of multitemporal and multiresolution images allows the method to be categorized as a relatively low-cost method compared to conventional surveys. This study compares SDB methods in deriving depth data using various machine learning algorithms using Sentinel-2A images in Kepulauan Seribu, Indonesia. Three machine learning algorithms were compared, namely K-Nearest Neighbors (KNN), Multiple Linear Regression (MLR), and Random Forest (RF), to observe the best-performing method. SDB was applied by combining echo-sounding measurements and the reflectance of blue, green, red, and near-infrared bands of Sentinel 2A. Our research revealed that RF provided the best accuracy compared to MLR and KNN. However, the resulted depth range could not cover very shallow water depth at 0 m. Only the MLR could detect zero depth, but it has the worst RMSE value. KNN provided a feasible result with slightly higher RMSE compared to RF, nonetheless, it took longer runtime for about 30% higher than RF.